BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2007)
Erysiphaceae of India - Monographic treatment - by Nasim Ahmed, O.K. agarwal, O.M. Bambawale and K.C. Puzari. Venus Printers and Publishers, New Delhi, 2007, pp. 109, Price Rs. 300.00. Â Disease Problems in Vegetable Production by S.K. Gupta and T.S. Thind; Scientific Publishers (India),Jodhpur, 2006, pp. 576, Price Rs. 275. Mushroom Cultivation Technology by Robin Gogoi, Y. Rathaiah and Tasvina Rahman Borah, Scientific Publishers (India), Jodhpur, Rajasthan, 130 pp., Rs. 250.00